MODERN MULTIMODAL APPROACHES TO THE DIAGNOSIS AND TREATMENT OF PRIMARY BRAIN TUMORS - Mamadaliev Abduraxmon Mamatkulovich (Research Focus International Scientific Journal, 2026)
Primary brain tumors represent a heterogeneous group of neoplasms with high clinical and social significance. Neuroepithelial tumors, particularly glial neoplasms, account for the majority of intracranial tumors and are characterized by aggressive biological behavior, high recurrence rates, and limited long-term survival despite advances in therapy. Modern diagnostic strategies rely heavily on neuroimaging modalities, primarily magnetic resonance imaging and computed tomography, with increasing interest in hybrid techniques combining MRI and positron emission tomography. Contemporary treatment paradigms are based on multimodal approaches integrating microsurgical resection, radiotherapy, chemotherapy, and emerging immunotherapeutic strategies. Radiotherapy remains a cornerstone of treatment for malignant central nervous system tumors, with fractionated regimens demonstrating optimal tumor control while minimizing neurocognitive toxicity. Advances in stereotactic radiosurgery and neuronavigation have significantly improved treatment precision and outcomes. Nevertheless, prognosis for high-grade gliomas remains poor, underscoring the need for personalized therapeutic strategies and further research into innovative treatment modalities.